Glossary of Virtual Reality Terminology - Manetta, Carol; Blade, Richard A. (International Journal of Virtual Reality, 1995)
The authors place the terms and definitions contained in this article into the public domain in order to elicit comments and discussion from readers. After much discussion and many modifications on the part of the Working Group on the VR Glossary, the revised glossary will be submitted as a IEEE draft standard. Then a VR Glossary Balloting Committee will be formed and ultimately vote on the inclusion of individual words and definitions into the IEEE Standard 100 Dictionary of Electrical and Electronic Terms.